POTENSI PENGEMBANGAN SADE SEBAGAI DESA WISATA LOMBOK - W. Suprihatin; H. Hailuddin (Jurnal Ekonomi dan Bisnis, 2016)
The background of the problems in this study is the decreasing quality of Sade hamlet amid rising tourist arrivals. From the environmental aspect, the conditions of the hamlet began to decline, in which the initial pattern of Sade has started a lot of changes towards the deficient and began to leave the local tradition. One effort to improve the condition of Sade hamlet in social, cultural and the environmental aspect is through the formulation of a sustainable structuring, the presence and identity maintaining and making a sustainable Tourism Village. Through analysis of AHP (Analytical Hierarchy Process) by collecting the perceptions of some experts through interviews and questionnaires, obtained by weighting the priority of the experts, namely the preservation of culture as an element of priority-level goals to be achieved in the development of Sade Hamlet as a tourist village at 0,476. While the determination of the level of the main criteria in the achievement of these objectives is the highest weight while maintaining a typical village environment at 0.319. Priority strategies that get the highest weight of the experts is that Sade Hamlet Revitalization with a priority weighting of 0.583. The second priority is the relocation of Hamlet at 0.235. Lowest weighting or last priority is Replication Sade Hamlet at 0.182.